Eficiência da produção técnica dos cursos de pós - graduação da UFC através de análise envoltória de dados - Pereira, Djalma Siqueira (2011)
The technical efficiency of production presents itself as a powerful tool to support decision making by providing tools for implementing actions that provide courses to graduate a better quality of teaching in their academic units. This work intends to analyze the technical efficiency of production of post-graduate of the UFC, with reference to the years 2007, 2008 and 2009 using DEA (Data Envelopment Analysis) - Data Envelopment Analysis. Other objectives that guided this study are: To provide information which could lead to increase actions to improve the methodology of intellectual production; Understanding the reasons why some courses to produce more and better than others so equated and growing; Provide grants to identify where efforts production should be concentrated. We applied the DMU (Decision Making Units) in the model that defines a boundary focused on efficient and inefficient units. In this application we used the DEA-CCR implemented by DEA-Solver software Pro8.0/CCR. Data were extracted from the Data Collection CAPES applications which meet the criteria for assessment of intellectual production, which highlights the nature of bibliographic production and concepts of distribution and production. The model uses as input variables: Number of Number of teachers and learners, and product variables: Total of papers; Publications in full proceedings; Publications in technical production, research projects, work completed dissertations, theses completed work; Average time of titration (months) master's mean titration (months) PhD. The results show that the comparison between the most efficient and least efficient show that the basic characteristic is the use of available resources that came to add more and better production. The production values of course have no direct relation with the number of teachers or students, because it caused a drop in production value by observing these values compared between efficient and inefficient.